PENGEMBANGAN MIKROLEARNING VIDEO 360° PADA FENOMENA RADIASI BENDA HITAM - Lestari, Tri Budy; Budi, Esmar; Fitri, Upik Rahma (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2024)
Universities are currently experiencing a paradigm shift in the acceptance of technology. Technology is seen as a complex and interconnected ecosystem, which facilitates the development of digital learning. This research aims to design and develop a 360° video microlearning on the phenomenon of black body radiation in modern physics courses as an efficient learning media. The research method used is Research & Development with reference to the ASSURE model modified into 4 stages. In this study, the sample used included 60 respondents from one class of physics education students and one class of physics students at UNJ. This study shows that the 360° video microlearning designed and developed can be an effective medium in helping students understand the phenomenon of blackbody radiation. The use of 360° video microlearning can have a significant impact in helping students to more easily understand the concept of black body radiation. With a visual and interactive approach, complex concepts can be simplified, thus facilitating the learning process. The final result of this research is a 360° video design that will be published on YouTube for easy access for users. After that, data collection was carried out using a validation questionnaire sheet to determine the feasibility of learning videos. Based on the validation results, the percentage of media feasibility was 96.42% and the percentage of material feasibility was 93.75%.